The study of skin lesions in Beluga (Huso huso) fed with different dietary levels of Aflatoxin B1 - Sepahdari, A.; Ebrahimzadeh Mosavi, H.A.; Motalebi, A.; Sharifpour, I.; Khosravi, A.R.; Kakoolaki, S.; Pourali, H.R.; Masomzadeh, A.; Hallajian, A. (2009)
In this study, 180 Beluga (Huso huso) weighing 120110g each with a stocking density of 12 fish per tank were adapted with synthetic diet and then fed with different levels of AFBI (0, 25, 50,75 & 100pplpikg of diets) under controlled conditions (T=1 8±2°C, DO=7.3ppm). The fish were fed 3% of their body weight four times a day for three months. Prevalence of skin lesions evaluated through clinical observations monthly. With regard to toxin concentration and time of exposure to AFBi in experimental fish, different degree of skin lesions (simple hemorrhage to progressive wounds) were observed in different parts of body especially in vent, caudal peduncle, fins, and head. "Yellow sores" on head and trunk regions were considerable and led to deterioration of appearance. Prevalence of skin lesion in different treatments was 8•m53.3%. After feeding with toxic diets was stopped, 16.w24% healing was obsenTed in the fish. Published